Endotracheal tube blockage during tracheo-oesophageal fistula surgery: A case report (Journal of Kathmandu Medical College, 2020)
The multifarious anaesthetic challenges associated with tracheo-oesophageal fistula surgery are difficult tracheal intubation, continuous air leakage during positive pressure ventilation, gastric distension, sharing of the airway with surgeons, intraoperative desaturation due to surgical retractors and maintaining anesthetic depth. These challenges are managed properly only when pathophysiology of the fistula is well understood. In this case report we present an anaesthetic management with a near miss situation during repair of tracheo-oesophageal fistula in a neonate. Intraoperatively, the patient’s oxygen saturation decreased which did not improve despite correcting all possible reasons. Before the worst could have occurred, we identified endotracheal tube blockage as the cause and changing the tube on time saved the neonate.